Peran Humas Dalam Membangun Hubungan Kerja Yang Harmonis Di IAIN Parepare - Sumarni Sumai; Iskandar Iskandar; Mifda Hilmiayah (Institut Agama Islam Negeri (IAIN) Curup, 2022)
In an organization that regulates and controls the communication system is Public Relations. This study aims to provide a comprehensive description and explanation of the role of Public Relations in building a harmonious working relationship at IAIN Parepare. To obtain an authentic understanding, this study uses a qualitative descriptive approach with procedures that produce descriptive data in the form of written or spoken words from people whose behavior is observed. The qualitative descriptive approach used in this research is a case study. The results of this study indicate: Broadly speaking, the duties of Public Relations at IAIN Parepare are divided into 3 (three); a) Implement socialization and promotion programs for institutions, b). Providing information and news services about the institution to the wider community, c). Carry out documentation of institutional activities. This task makes Public Relations at IAIN Parepare act as a journalist in an organization that only provides technical communication services. 2. Public relations at IAIN Parepare has not been able to carry out its ideal role in building harmonious working relationships through two-way communications. Both Public Relations as a source of information (source of informations) and Public Relations as a channel of information (channel of informations) for the internal and external public.